(untitled) (Statistics, Optimization & Information Computing, 2025)
In this paper, we propose a random (b, θ)-enriched contraction operator and prove an existence theorem of random fixed points for this operator. Moreover, we establish an existence result for a solution to a nonlinear stochastic integral equation of Hammerstein type.